Analisis Fenomena Postpartum Depression dalam Perspektif Al-Qur’an : Studi Tentang Pola Asuh - Iffah; Iffah Najmi Maryam (EduInovasi: Journal of Basic Educational Studies, 2025)
Postpartum depression is a continuation of the condition experienced by mothers after childbirth, commonly known as baby blues. Baby blues are common among postpartum mothers due to a sharp decline in hormones, leading to significant emotional or mood changes felt by the mother. It is mentioned in the Qur'an, in Surah Al-Baqarah verse 233, the command to pay more attention to mothers after childbirth, as this period is very fragile for a mother, considering the immense struggle and risk to her life during childbirth. The verse states, "And the duty of the father is to provide for the mothers with food and clothing in a fair manner," highlighting the father's responsibility to support the mother appropriately, as the child carries his name. Hence, this duty should be carried out justly. However, to this day, many parents do not fully understand the correct parenting methods as exemplified in the Qur'an, leading to imbalances in parenting practices, which are often solely burdened on the mother. This raises the question of how the Qur'an addresses the phenomenon of postpartum depression and what constitutes proper parenting to prevent mothers from experiencing postpartum depression. The method used in this research is descriptive qualitative and is library-based, exploring verses related to postpartum depression and parenting. It employs a thematic tafsir approach, interpreting Qur'anic verses according to the studied theme. The Qur'an provides insights into the emotional conditions and various negative emotions that a mother may experience postpartum. It also emphasizes the importance of giving love, attention, and support to maintain the mental health of mothers after childbirth. Verses explaining parenting in terms of education, faith, morality, and etiquette are conveyed through the figure of the father. This indicates that in the parenting process, the father is responsible for imparting knowledge to the child. In this parenting process, creating a balance between the roles of the father and the mother can prevent postpartum depression in the mother. Implementing fair parenting practices in accordance with Qur'anic values can play a significant role in reducing the risk of postpartum depression.